HUBUNGAN ANTARA PEMAHAMAN TENTANG HAM DENGAN SIKAP TOLERANSI PADA SISWA KELAS VIII SEMESTER GENAP SMP NEGERI 4 NEGARA TAHUN PELAJARAN 2016/2017 - Arie Ramadhani; Dewi Ria Agustin (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2017)
Human rights education spurs students to be able to develop strong self-tolerance attitudes, this is because students will realize that as human beings they are social beings besides individual beings so they are aware that besides them there are still others who need and need them in their daily lives - day. The formulation of the problem in this study is whether there is a relationship between students' understanding of human rights and the attitude of tolerance of students in Class VIII Even Semester of State Middle School 4 Country 2016-2017. The researcher used data analysis methods with statistics. The statistical formula used is the tetrachoric relationship technique. To test the significance of the coefficient of the tetrachoric relationship (r t) it is tested with the Producer Moment (Ò²2). The results of his research are that there is a relationship between understanding of human rights and the attitude of tolerance in Class VIII students in the even semester of SMP Negeri 4 in Academic Year 2016-2017, because r = 0.601 is in the range of 0.600 - 0.800 included in the Relationship.